Breakthroughs in neuroactive steroid drug discovery. Issue 2 (15th January 2018) - Blanco, Maria-Jesus; La, Daniel; Coughlin, Quinn; Newman, Caitlin A.; Griffin, Andrew M.; Harrison, Boyd L.; Salituro, Francesco G.
Graphical abstract: Abstract: Endogenous and synthetic neuroactive steroids (NASs) or neurosteroids are effective modulators of multiple signaling pathways including receptors for the γ-aminobutyric acid A (GABAA ) and glutamate, in particular N -methyl-d -aspartate (NMDA). These receptors are the major inhibitory and excitatory neurotransmitters in the central nervous system (CNS), and there is growing evidence suggesting that dysregulation of neurosteroid production plays a role in numerous neurological disorders. The significant unmet medical need for treatment of CNS disorders has increased the interest for these types of compounds. In this review, we highlight recent progress in the clinical development of NAS drug candidates, in addition to preclinical breakthroughs in the identification of novel NASs, mainly for GABAA and NMDA receptor modulation.